Exosomes as renal inductive signals in health and disease, and their application as diagnostic markers and therapeutic agents - Krause, Mirja; Samoylenko, Anatoliy; Vainio, Seppo J. (Frontiers in Cell and Developmental Biology, 2015)
Cells secrete around 30-1000 nm membrane-enclosed vesicles, of which members of the subgroup between 30-100 nm are termed exosomes (EXs). EXs are released into the extracellular space and are widely present in body fluids and incorporated mRNA, miRNA, proteins and signaling molecules. Increasing amounts of evidence suggest that EXs play an important role not only in cell-to-cell communication but also in various physiological and disease processes. EXs secreted by kidney cells control nephron function and are involved in kidney diseases and cancers. This makes them potential targets for diagnostic and therapeutic applications such as non-invasive biomarkers and cell-free vaccines and for use as drug delivery vehicles. This review provides an overview on the known roles of EXs in kidney development and diseases, including renal cancer. Additionally, it covers recent findings on their significance as diagnostic markers and on therapeutic applications to renal diseases and cancers. The intention is to promote an awareness of how many questions still remain open but are certainly worth investigating.